2009
DOI: 10.1086/595793
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Toxoplasmosis and Reinfection during Pregnancy: Case Report, Strain Characterization, Experimental Model of Reinfection, and Review

Abstract: We present a case of disseminated congenital toxoplasmosis in a newborn born to a mother who had been immunized against toxoplasmosis before conception. The mother was reinfected, likely by ingestion of imported raw horse meat during pregnancy. This clinical presentation is exceptional in France and raised the possibility of infection by a highly virulent Toxoplasma strain. The strain responsible was isolated from the peripheral blood of the newborn, and when genotyped with microsatellite markers, it exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
117
0
30

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(150 citation statements)
references
References 33 publications
3
117
0
30
Order By: Relevance
“…This belief is changing because of greater genetic diversity as a result of sexual recombination of the parasite (Su et al 2010;Khan et al 2011). A recent study indicated that congenital T. gondii can occur in immune mothers (seropositive) when an atypical genotype overcomes the acquired resistance from the original infecting genotype (Elbez-Rubinstein et al 2009). Moreover, a study recently demonstrated a severe form of congenital T. gondii in children of non-immune mothers in the third trimester (Delhaes et al 2010), which is rarely caused by the typical genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This belief is changing because of greater genetic diversity as a result of sexual recombination of the parasite (Su et al 2010;Khan et al 2011). A recent study indicated that congenital T. gondii can occur in immune mothers (seropositive) when an atypical genotype overcomes the acquired resistance from the original infecting genotype (Elbez-Rubinstein et al 2009). Moreover, a study recently demonstrated a severe form of congenital T. gondii in children of non-immune mothers in the third trimester (Delhaes et al 2010), which is rarely caused by the typical genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, women demonstrating exposure to T. gondii prior to pregnancy through serology were considered safe from future infection and risk to the fetus. However, apparent recrudescent infections during pregnancy can occur in immunocompetent mother although few cases have been reported [10]. A case of maternal T. gondii infection and subsequent fetal infection was reported in a 31-year old French woman with serological evidence of previous T. gondii exposure.…”
Section: Toxoplasmosis In Cats and Other Animalsmentioning
confidence: 99%
“…Recently, attention has been focused on the genetic variability among T. gondii isolates from apparently healthy and sick hosts (Howe et al, 1997;Grigg and Sundar, 2009). Severe cases of toxoplasmosis have been reported in immunocompetent patients in association with atypical T. gondii genotypes (Ajzenberg et al, 2004;Demar et al, 2007;Elbez-Rubinstein et al, 2009;Grigg and Sundar, 2009;Vaudaux et al, 2010;Wendte et al, 2010).…”
Section: Genetic Diversity and Epidemiological Significancementioning
confidence: 99%